Pengembangan LKS Pembuatan VCO (Virgin Coconut Oil) secara Enzimatis pada Pokok Bahasan Implikasi Bioteknologi Di Kelas XII IPA SMA - AYU DEWI PRAMITA (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2013)
This research aims to 1) produce student worksheets making VCO enzymatically, 2) produce VCO enzymatically of fruits and leaf, 3) describe the feasibility, 4) describe result of students process skills observation in group and 5) describe the response of student worksheets has been developed. Development of student worksheets using 4-D models include define, design, develope, and disseminate, but in this study only conducted to develope stage. In the design stage begins with finding literature on proteolytic enzyme or protease contained in fruits and plants. After literatures study, conducted by making VCO based materials have been obtained. The results showed that results of VCO obtained by the addition of enzyme aloe leaf have criteria VCO is good through organoleptic tests are clear color, the aroma is typical coconut and tastes like regular oil. That results of VCO used in the development of student worksheets is melon, cucumber and aloe leaf have criteria are clear color, the aroma is not overpowering and tastes like regular oil. Trial of student worksheets implemented at SMA Bina Bangsa Surabaya by the number of students is 14 children. The student worksheets categorized decent with mean score of 3.69 with range of 1-4. Student worksheets developed to get a positive response by 90.72% and observation of students process skills in group during the making of VCO is less-excellent with a score between 40-100% with the score range 1-100%. Keywords: Development of Student Worksheets, VCO, enzimatically, Biotechnology